A Mutation in the N Domain of Escherichia coli Lon Stabilizes Dodecamers and Selectively Alters Degradation of Model Substrates - Wohlever, Matthew L. (American Society for Microbiology, 2013)
Escherichia coli Lon, an ATP-dependent AAA(+) protease, recognizes and degrades many different substrates, including the RcsA and SulA regulatory proteins. More than a decade ago, the E240K mutation in the N domain of Lon was shown to prevent degradation of RcsA but not SulA in vivo. Here, we characterize the biochemical properties of the E240K mutant in vitro and present evidence that the effects of this mutation are complex. For example, Lon(E240K) exists almost exclusively as a dodecamer, whereas wild-type Lon equilibrates between hexamers and dodecamers. Moreover, Lon(E240K) displays degradation defects in vitro that do not correlate in any simple fashion with degron identity, substrate stability, or dodecamer formation. The Lon sequence segment near residue 240 is known to undergo nucleotide-dependent conformational changes, and our results suggest that this region may be important for coupling substrate binding with allosteric activation of Lon protease and ATPase activity.